Stratospheric Balloon Observations of Infrasound Waves From the 15 January 2022 Hunga Eruption, Tonga. Issue 19 (7th October 2022) - Podglajen, Aurélien; Le Pichon, Alexis; Garcia, Raphaël F.; Gérier, Solène; Millet, Christophe; Bedka, Kristopher; Khlopenkov, Konstantin; Khaykin, Sergey; Hertzog, Albert
Abstract: The 15 January 2022 eruption of the Hunga volcano (Tonga) generated a rich spectrum of waves, some of which achieved global propagation. Among numerous platforms monitoring the event, two stratospheric balloons flying over the tropical Pacific provided unique observations of infrasonic wave arrivals, detecting five complete revolutions. Combined with ground measurements from the infrasound network of the International Monitoring System, balloon‐borne observations may provide additional constraint on the scenario of the eruption, as suggested by the correlation between bursts of acoustic wave emission and peaks of maximum volcanic plume top height. Balloon records also highlight previously unobserved long‐range propagation of infrasound modes and their dispersion patterns. A comparison between ground‐ and balloon‐based measurements emphasizes superior signal‐to‐noise ratios onboard the balloons and further demonstrates their potential for infrasound studies. Plain Language Summary: The eruption of the Hunga volcano on 15 January 2022 was one of the most powerful blasts of the last century. This fast and strong perturbation of the atmosphere triggered atmospheric waves which were followed around the world multiple times. Here, we use records of sound waves emitted by the eruption from two balloons flying at about 20 km altitude over the Pacific combined with ground stations around the volcano to help characterize the event and its scenario. Due to weak relative wind and turbulence, the sounds on the balloon are generally clearer than on the ground, demonstrating the potential of high‐altitude measurements for extreme events. Key Points: Comparison between balloon‐borne and ground‐based observations of infrasound waves triggered by the January 2022 Hunga eruption Eruption sequence from infrasound in broad agreement with plume top height evolution Benchmark for long‐range monitoring of infrasound from large explosive sources using stratospheric balloon observations